Multi-channel groupwise registration to construct an ultrasound-specific fetal brain atlas - Namburete, A; Van Kampen, R; Papageorghiou, A; Papież, B (Springer, Cham, 2018)
In this paper, we describe a method to construct a 3D atlas from fetal brain ultrasound (US) volumes. A multi-channel groupwise Demons registration is proposed to simultaneously register a set of images from a population to a common reference space, thereby representing the population average. Similar to the standard Demons formulation, our approach takes as input an intensity image, but with an additional channel which contains phase-based features extracted from the intensity channel. The proposed multi-channel atlas construction method is evaluated using a groupwise Dice overlap, and is shown to outperform standard (single-channel) groupwise diffeomorphic Demons registration. This method is then used to construct an atlas from US brain volumes collected from a population of 39 healthy fetal subjects at 23 gestational weeks. The resulting atlas manifests high structural overlap, and correspondence between the US-based and an age-matched fetal MRI-based atlas is observed.